Identification of wysPII as an Activator of Morphological Development in Streptomyces albulus CK-15 - Liu, Binghua; Ge, Beibei; Ma, Jinjin; Wei, Qiuhe; Khan, Abid Ali; Shi, Liming; Zhang, Kecheng (Frontiers in Microbiology, 2018)
Wuyiencin, which is produced by Streptomyces albulus var. wuyiensis, has been widely used to in agriculture to control a variety of fungal diseases, such as cucumber downy mildew, strawberry powdery mildew, and botrytis cinerea. As an industrially-produced biopesticide, reducing production costs is very important for popularization of this approach. To obtain a rapidly growing strain that effectively shortens the fermentation time, we investigated the effects of knockdown and overexpression of the wysPII gene, a novel member of the LuxR family of regulatory genes, in S. albulus strain CK-15. The ∆wysPII mutant exhibited growth retardation and reduced sporulation, while the ooPII strain exhibited much more rapid growth and increased sporulation compared with the wild-type strain. The ooPII reached a plateau stage of maximum biomass at 54 h, which was 18 h faster than that of the wild-type strain. Furthermore, the wysPII was shown to act as an activator of morphological development without affecting wuyiencin production. Thus, the ooPII strain can be used to reduce costs and increase efficiency in industrial fermentation production processes.